2005
DOI: 10.1097/00000542-200507000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Postincisional Allodynia by Subcutaneous Bupivacaine

Abstract: Incision of rat hairy skin changes pain responses, similar to pain in humans. Preincisional subcutaneous bupivacaine selectively suppresses and shortens allodynia for times far outlasting its local anesthesia, an effect largely from systemic actions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…Incisions on the back increased the local responses to tactile punctate stimulation with von Frey filaments, as reported previously (Duarte et al, 2005). Primary and secondary hyperesthesia were apparent at the first testing, 0.5 hour after incision, (Figs.…”
Section: Tactile Sensitivity and Post-incisional Hyperesthesia Of Haisupporting
confidence: 86%
See 3 more Smart Citations
“…Incisions on the back increased the local responses to tactile punctate stimulation with von Frey filaments, as reported previously (Duarte et al, 2005). Primary and secondary hyperesthesia were apparent at the first testing, 0.5 hour after incision, (Figs.…”
Section: Tactile Sensitivity and Post-incisional Hyperesthesia Of Haisupporting
confidence: 86%
“…We and others have previously shown that central sensitization appears after incision in rat hairy skin, as evidenced by the actions of systemic local anesthetics on post-incisional pain (Duarte et al, 2005) and by recordings from high threshold and low threshold afferents as well as wide dynamic range (WDR) spinal cord neurons (Kawamata et al, 2005). During incision and suturation an increase in activity was recorded in all three classes of spinal neurons, but spontaneous activity and that evoked by light tactile stimulation, as is used to assess allodynia, for several hours after surgery was only prominent in the WDR neurons (Kawamata et al, 2005).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Second, despite the fundamental differences in mechanism of action, basic science investigations suggest that both local anesthetic agents and Cox inhibitors decrease peripheral and central sensitization via a direct central nervous system effect [12,13]. When administered systemically to decerebrate animals, local anesthetics decrease dorsal horn neuronal excitability [12,14]. In addition, it is possible that repeated local anesthetic wound instillation decreases injury-induced C-fiber activity with a resultant decrease in peripheral and central sensitization [13].…”
Section: Discussionmentioning
confidence: 99%